2017
DOI: 10.1111/jon.12477
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Inflammation in Acute Intracerebral Hemorrhage with PK11195 PET and Dynamic Contrast‐Enhanced MRI

Abstract: BACKGROUND AND PURPOSE Studies in animal models suggest that inflammation is a major contributor to secondary injury after intracerebral hemorrhage (ICH). Direct, noninvasive monitoring of inflammation in the human brain after ICH will facilitate early‐phase development of anti‐inflammatory treatments. We sought to investigate the feasibility of multimodality brain imaging in subacute ICH. METHODS Acute ICH patients were recruited to undergo multiparametric MRI (including dynamic contrast‐enhanced measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…With the advent of total-body PET clinical scanners (57), assessment of multiorgan responses to disease will become increasingly important in medical research. This is attractive for TSPO-PET studies, given that TSPO has served as a marker of regional tissue inflammation in pathologies throughout the body (4,(6)(7)(8)(9)(10). In this study, we observed a significant positive correlation between the brain and heart following MI, which was detected by 18 F-LW223 PET imaging in vivo, and TSPO and CD68 staining ex-vivo.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…With the advent of total-body PET clinical scanners (57), assessment of multiorgan responses to disease will become increasingly important in medical research. This is attractive for TSPO-PET studies, given that TSPO has served as a marker of regional tissue inflammation in pathologies throughout the body (4,(6)(7)(8)(9)(10). In this study, we observed a significant positive correlation between the brain and heart following MI, which was detected by 18 F-LW223 PET imaging in vivo, and TSPO and CD68 staining ex-vivo.…”
Section: Discussionmentioning
confidence: 50%
“…The 18kDa translocator protein (TSPO) is expressed within the outer membrane of the mitochondria (3) where it is a key factor in controlling the transport of cholesterol necessary for steroid hormone synthesis. TSPO is highly expressed within inflammatory cells such as macrophages in the periphery (4) and microglia in the brain (5), and has consequently been used as a marker of inflammation in pathologies throughout the body (4,(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the degree of cerebral inflammation after acute hemorrhage via positron emission tomography (PET), Abid et al utilized [ 11 C]-(R)-PK11195 to highlight the perihematomal region [ 92 ]. [ 11 C]-(R)-PK11195 attaches to translocator protein 18 kDa (TSPO), whose level is promptly increased in activated microglia.…”
Section: Microglia In Arteriovenous Malformations and Cavernomas—an Ongoing Enigmamentioning
confidence: 99%
“…However, until very recently no such effort has been made after ICH. To this end, a study comprising of five ICH patients documented for the first time the feasibility of employing [ 11 C] labeled first generation TSPO ligand, [ 11 C]-(R)-PK11195 in monitoring microglial activation after ICH (Abid et al, 2017 ). However, given the small sample size of the aforementioned study (Abid et al, 2017 ), future work is highly warranted establishing the applicability of TSPO ligands for neuroimaging applications after ICH.…”
Section: Can Tspo Be Targeted For Neuroimaging After Ich?mentioning
confidence: 99%